Today’s Insurance Market and Prospects of Digital Insurance - Yu. T. Akhvlediany (Вестник Российского экономического университета имени Г. В. Плеханова)
Russian insurance market has adapted to macro-economic and geo-political situation and now can be characterized by stable and sustainable development. The article studies today’s development of insurance market, identifies prospects of insurance service digitalization and analyzes digital maturity of insurance companies. The author advanced his own approach to finding ways of transforming insurance business with regard to global goals of insurance market development. A conclusion was drawn that digital technologies in insurance are essential for the efficiency of the finance system, as they foster the development of insurance market and improve quality of insurance services. By analyzing digital insurance the author highlighted the importance of further introduction of digital technologies in insurance industry in order to upgrade quality of insurants’ protection and develop insurance market in conditions of digital economy.